(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
This article examines the implementation of innovative technologies in the training process for track and field athletics, which represents a key area in the advancement of modern sports. The continuous intensification of athletic competition and the increasing demands to the technical preparation of track and field athletes necessitate the implementation of cutting-edge technological solutions. Particular emphasis has been placed on the role of digital tools in motor skill acquisition enhancement, athletes’ technical proficiency improvement, physical performance optimization, and training methodologies personalization. The role of interactive training platforms and biomechanical motion analysis systems in facilitating a detailed assessment of exercise techniques has been analyzed. The feasibility of employing video analysis and biomechanical trackers has been substantiated, highlighting their effectiveness in identifying technical errors, refining movement patterns, and adapting training loads to the individual characteristics of athletes. The effectiveness of digital technologies in the preparation of young athletes is underscored, as these tools aid in mastering technically complex elements, fostering correct motor execution, and increasing motivation for training. Additionally, the article considers the integration of virtual and augmented reality systems, which simulate competitive environments and provide interactive feedback, thereby enhancing psychological resilience and concentration among athletes. Special attention has been paid to the application of artificial intelligence (AI) in track and field training. AI is recognized for its capability to analyze large datasets related to athletes’ physical condition, biomechanical parameters, and technical performance, enabling personalized training regimens, preventing overtraining, and predicting athletic results. The conclusions highlight the significance of integrating innovative technologies with scientifically grounded methodological approaches to achieve high performance in track and field athletics. The application of advanced tools contributes to refining exercise techniques, reducing the risk of injuries, unlocking athletic potential, and maintaining an optimal level of technical proficiency among athletes.